Intraarticular Allogenic Mesenchymal Stem Cells and Vascular Endothelial Growth Factor Injection in Anterior Cruciate Ligament Reconstruction - Utomo, Dwikora Novembri; Mahyudin, Ferdiansyah; Zulkarnain, Arif; Purwati, Purwati; Setyawati, Rossy (Folia Medica Indonesiana, 2020)
Graft tunnel healing is important for the successful reconstruction of the anterior cruciate ligament by using the hamstring tendon autograft. There are studies that intra graft tunnel Bone Marrow Mesenchymal stem cells (BMSCs) or intra graft tunnel Vascular endothelial growth factor (VEGF) accelerated graft tunnel healing. This study aimed to investigate the effect of using BMSCs+VEGF injected intra-articular on graft tunnel healing. We reconstructed the anterior cruciate ligament (ACL) of 12 rabbits using an autograft hamstring tendon with and without intra-articular BMSCs+VEGF. Histological evaluation was done at 3 and 6 weeks after ACL reconstruction. On the surface between the graft and the bone tunnel obtained collagen fiber thickness or Sharpey fiber is significantly more than the control group (p< 0.05) in the evaluation of 3 weeks and 6 weeks either side of the tibia and the femur. To evaluate the progression of the treatment, treatment group and control group gained progression had significantly when compared to 3 weeks and 6 weeks. It can be concluded that intra-articular injection of VEGF+BMSCs can accelerate the integration of the graft tunnel from histology evaluation on 3 and 6 weeks.